Implementasi Pembelajaran Aktif dalam Proses Kegiatan Belajar Mengajar (KBM) di Pesantren - M. Yusuf (AKSI: Jurnal Manajemen Pendidikan Islam, 2022)
This research examines how an educator can activate students in classroom learning, and to get there, it is necessary to understand that the task of an educator is not easy, they are required to encourage students to be active in learning without having to rely on control and control. supervision of an educator. The purpose of this study is how teachers are able to activate students in learning by paying attention to several factors that are considered to make learning conducive. The method used is library research by examining several theories in depth. The results of this study are active learning is learning that involves the activeness of students in finding something that is used as a finding and a new view based on independent activities that come from within the student. Learning objectives refer to the three domains inherent in students, namely cognitive, affective, and psycomotor. The implementation of active learning can be carried out in various steps, including mastering the class, recognizing all the names and backgrounds of students, giving full and detailed attention to students, changing the language of books to daily language in learning, and giving varied assignments.